Transformacje tożsamości żydowskich emigrantów na podstawie wywiadów Teresy Torańskiej z tomu "Jesteśmy. Rozstania`68" = "Jesteśmy. Rozstania`68" ["We are. The farewells of `68"] by Teresa Torańska. Transformations of Jewish emigrants` identities - Rostkowska, Kaja (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The aim of this article is to attempt to examine the transformations of identities which can be seen in the heroes of a book by Teresa Torańska entitled "Jesteśmy. Rozstania`68", i.e. Jewish emigrants of Polish origin.
Keywords: tożsamość; tożsamość aktywna; tożsamość pasywna; tożsamość deliberatywna; memetyka; identyfikacja; samoidentyfikacja; język; językoznawstwo; językoznawstwo polskie